2022
DOI: 10.1038/s41590-022-01208-z
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-targeted gene delivery of interleukin 2 specifically increases brain-resident regulatory T cell numbers and protects against pathological neuroinflammation

Abstract: The ability of immune-modulating biologics to prevent and reverse pathology has transformed recent clinical practice. Full utility in the neuroinflammation space, however, requires identification of both effective targets for local immune modulation and a delivery system capable of crossing the blood–brain barrier. The recent identification and characterization of a small population of regulatory T (Treg) cells resident in the brain presents one such potential therapeutic target. Here, we identified brain inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 69 publications
2
75
0
Order By: Relevance
“…Due to its potent immunomodulatory functions, IL-2 has been also evaluated for clinical purposes in disparate settings, and in a recent study (Yshii et al, 2022) Yshii and colleagues elegantly described a brain-specific IL-2 delivery system capable of protecting mice from pathological neuroinflammation of the central nervous system, a non-lymphoid tissue where also B cells can be recruited and play critical roles (Ahn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its potent immunomodulatory functions, IL-2 has been also evaluated for clinical purposes in disparate settings, and in a recent study (Yshii et al, 2022) Yshii and colleagues elegantly described a brain-specific IL-2 delivery system capable of protecting mice from pathological neuroinflammation of the central nervous system, a non-lymphoid tissue where also B cells can be recruited and play critical roles (Ahn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The target gene expression can be detected within 30 min after nontoxic Dox added and maximal expression levels can be higher than expression levels obtained from the CMV promoter 42 . Therefore, the Tet‐on system has been applied to develop a tissue‐specific delivery system on cell therapy and generate controllable transgene expression systems to produce animal models of disease 43–45 . Herein, we first generated inducible cell lines to quantify ZIKV C–C interaction based on the SLCA and Tet‐on system.…”
Section: Discussionmentioning
confidence: 99%
“…42 Therefore, the Tet-on system has been applied to develop a tissuespecific delivery system on cell therapy and generate controllable transgene expression systems to produce animal models of disease. [43][44][45] Herein, we first generated inducible cell lines to quantify It has been shown recently that α-helix-mediated protein-protein interactions are promising drug targets that can be affected by various types of inhibitors including peptides, foldamers, and proteomimetic-derived ligands. 46 To verify the specificity of the inducible system, we have tested the inhibitory effect of potential peptide inhibitors of ZIKV C-C interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is thought to be related to inflammation. Lidia Yshii and others have found that IL-2 level is a limiting factor for Tregs in the human brain, and brain-specific IL-2 delivery is an effective strategy to suppress neuroinflammation [ 15 ]. The objectives of this review are to explore the possible impact of IL-2 on the prevalence and progression of schizophrenia, as well as the potential of IL-2 to be used as a marker of schizophrenia in order to provide novel insights for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%